2021
DOI: 10.2478/jped-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Searching for learners’ voices: Teachers’ struggle to align pedagogical-reform policy with instructional practice

Abstract: Globally, pedagogical reform policy seeks to give space to learners’ voices. But teachers often struggle to engage learners in knowledge construction, deconstruction and reconstruction; as advocated by official curriculum reform policy. Aligning classroom practice to pedagogical-reform policy remains an uphill struggle for most teachers. This article examines Zimbabwean teachers’ efforts to align teaching methods to new curriculum policy which seeks to engage learners in classroom discourse. Using a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This passivity must have made the students rate their teachers low in the use of instructional materials since they were not actively engaged during teaching and learning. This situation was also recorded by Chimbi and Jita [20] who remarked that the use of a teacher-centered method for instruction was still popularly used in secondary schools. This result disagrees the findings of previous researchers [18], [33] who found that teachers scored a little average in their use of instructional materials and the laboratory as rated by their students.…”
Section: Research Question 1: How Do Physics Students Rate Physics Te...mentioning
confidence: 76%
See 3 more Smart Citations
“…This passivity must have made the students rate their teachers low in the use of instructional materials since they were not actively engaged during teaching and learning. This situation was also recorded by Chimbi and Jita [20] who remarked that the use of a teacher-centered method for instruction was still popularly used in secondary schools. This result disagrees the findings of previous researchers [18], [33] who found that teachers scored a little average in their use of instructional materials and the laboratory as rated by their students.…”
Section: Research Question 1: How Do Physics Students Rate Physics Te...mentioning
confidence: 76%
“…One important stakeholder whose feedback and opinions have usually been neglected in teachinglearning is the learner [20], [21]. Learners often struggle for relevance because their voices on teacherlearning matters are not heard.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations